Pengaruh Kualitas Pelayanan terhadap Kepuasan pada PT. Telekomunikasi Indonesia Cabang Baubau: The Effect of Service Quality on Satisfaction at PT. Telecommunications Indonesia Baubau Branch - Abdullah, Rudi (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this research is to know how the influence of service quality to satisfaction at PT Telekomunikasi Indonesia Branch Baubau. With the initial hypothesis that the quality of service affect the satisfaction. With a sample size of 39 people using a simple regression analysis and then descriptive. Based on analysis of research results and discussion in this study, it can be concluded that the quality of service is very influential on satisfaction at PT Telekomunikasi Indonesia Branch Baubau. This can be seen from the regression equation Y = 5.833 + 0.686 X This shows that if there is a change in service quality dimension of I unit, it will cause changes to the satisfaction of 68.6%. Quality of service influence on satisfaction can be seen from the significance value t on a simple regression analysis that sig t = 0.00 <a = 0.05. The value of correlation coefficient (R) of 0.809 can be interpreted that the correlation relationship between service quality independent variable (X) to satisfaction (Y) is positive.